(3eaGJjM GdQVhGf aj JaSjQ GdbQBf HGdbQBfs - (3eMeO Hf ESeGYjd Hf UdGM Hf eMeO GdMSfj, GdcMdGfj Ke GdUfYGfj, CHh EHQGgje, YR GdOjf, GdeYQha cCSdGag HGdCejQ, J (B1182 (3g` s
(3ChdgG (B:s
(3jHOC HJaSjQ ShQI GdTYQGA s
(3BNQgG (B:s
(3jfJgi HJaSjQ ChGFd ShQI dbeGf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B38s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B520s
Keywords: (3GdJaSjQ hYdhe GdbQBfs